Three hypervelocity white dwarfs in Gaia DR2: evidence for dynamically driven double-degenerate double-detonation type Ia supernovae - Shen, Ken J.; Boubert, Douglas; Gänsicke, Boris T.; Jha, Saurabh W.; Andrews, Jennifer E.; Chomiuk, Laura; Foley, Ryan J.; Fraser, Morgan; Gromadzki, Mariusz; Guillochon, James; Kotze, Marissa M.; Maguire, Kate; et al. (The astrophysical journal, 2018)
Double detonations in double white dwarf (WD) binaries undergoing unstable mass transfer have emerged in recent years as one of the most promising Type Ia supernova (SN Ia) progenitor scenarios. One potential outcome of this “dynamically driven double-degenerate double-detonation” (D6) scenario is that the companion WD survives the explosion and is flung away with a velocity equal to its >1000 km s−1 pre-SN orbital velocity. We perform a search for these hypervelocity runaway WDs using Gaia's second data release. In this paper, we discuss seven candidates followed up with ground-based instruments. Three sources are likely to be some of the fastest known stars in the Milky Way, with total Galactocentric velocities between 1000 and 3000 km s−1, and are consistent with having previously been companion WDs in pre-SN Ia systems. However, although the radial velocity of one of the stars is >1000 km s−1, the radial velocities of the other two stars are puzzlingly consistent with 0. The combined five-parameter astrometric solutions from Gaia and radial velocities from follow-up spectra yield tentative 6D confirmation of the D6 scenario. The past position of one of these stars places it within a faint, old SN remnant, further strengthening the interpretation of these candidates as hypervelocity runaways from binary systems that underwent SNe Ia.
Gesehen am 01.10.2019